Lipid and immunophenotypic profiles in hemodialysis patients with citrate vs. acetate dialysates - Rodríguez-Espinosa, Diana; Cuadrado-Payán, Elena; Morantes, Laura; Gomez, Miquel; Maduell, Francisco; Broseta, José Jesús (Frontiers in Cardiovascular Medicine, 2025)
BackgroundChronic kidney disease (CKD) is a significant cardiovascular (CV) risk factor, with dialysis-dependent CKD (DD-CKD) patients facing high mortality rates. Hypercholesterolemia is another crucial CV risk factor, typically managed with lipid-lowering therapy, though its efficacy in DD-CKD remains uncertain. Evidence shows mixed results regarding the benefits of statins in these patients. Citrate-based dialysates are known to reduce inflammatory biomarkers compared to acetate-based ones, potentially impacting lipid profiles and immune responses. This study aimed to determine the effects of citrate vs. acetate dialysate on lipid profiles and immunophenotypes in DD-CKD patients.MethodsThis unicentric, cross-over, prospective study included 21 hemodialysis patients (10 males, 11 females, average age 62.25 years). Each patient underwent 24 dialysis sessions (12 with each dialysate) and acted as their own control. Lipid profiles, immunological parameters, and nutritional and inflammatory markers were measured before the last session with each dialysate.ResultsAfter twelve dialysis sessions with citrate dialysate (CD), compared to acetate dialysate (AD), there was a statistically significant decline in TG and remnant cholesterol, with a decrease in HDL and an increase in LDL. Regarding immunology, C3 complement levels were higher, while CD3+ CD8+ and CD16+ 56+ lymphocytes were lower. Finally, total lymphocytes were lower with AD than with CD. We found no difference in predialysis nutritional nor inflammatory parameters except for ESR, which was higher when subjects used CD than AD.ConclusionThere are significant differences in lipid and immunophenotypic profiles with CD in comparison to AD. Interestingly, there could be an advantageous profile given the reduced amount of remnant cholesterol and TG. However, further studies are needed to understand if the observed changes lead to beneficial hard clinical outcomes in DD-CKD patients.